Pemanfaatan E-Government Dalam Peningkatan Kinerja Pegawai Pada Pemerintah Kabupaten Mamuju - Ramadhani, Anita; Shaddiq, Syahrial (Pascasarjana Universitas Muhammadiyah Mamuju, 2024)
The introduction of e-Government as information and communication technology in government brings further improvements in government organization and operations. This aims to enable employees to carry out and carry out their duties and functions effectively and efficiently. This research uses a qualitative approach. Data was obtained from interviews, observations, and documents. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of this research show that the use of e-Government introduced by the Mamuju Regency Government in the OPD service section provides benefits to employee performance in providing existing services to the community, based on good and effective service delivery. There is a possibility that this will happen and will also enable increased efficiency and consistent provision of information to the public. The government needs to further increase existing resources to support performance. Because this is one of the factors that influences how well you utilize e-Government to more actively monitor community activity on existing platforms and social media, ensure communities receive faster responses from staff, and activate existing programs to provide quality information.